Dysconnectivity between the anterior insula and the dorsal anterior cingulate cortex during an emotion go/nogo paradigm is associated with aggressive behaviors in male schizophrenia patients. (January 2023) - Fortier, Alexandra; Dumais, Alexandre; Athanassiou, Maria; Tikàsz, Andràs; Potvin, Stéphane
Highlights: Patients with schizophrenia show aberrant connectivity during an emotional Go/No-Go task. Altered connectivity pertained to brain regions involved in cognitive control, emotion processing. Connectivity data was related to aggressive behaviors in schizophrenia. Abstract: This study aimed to investigate the association between past-reported violent/aggressive behaviors and brain functional connectivity in male patients suffering from schizophrenia using a task modeling the interaction between negative emotion processing and response inhibition. Forty-four male patients with schizophrenia and twenty-two healthy male controls performed an emotional go/no-go task using angry and neutral faces during a functional magnetic resonance imaging session. Generalized psycho-physiological interaction was conducted to explore task-based functional connectivity and a negative binomial regression was used to evaluate the relationship between neural alterations and violent/aggressive behaviors. Regions involved in response inhibition and emotion regulation, such as the anterior insula, dorsal anterior cingulate cortex (dACC) and dorsolateral prefrontal cortex (DLPFC), were used as seed regions. During emotion-related response inhibition, patients with schizophrenia displayed altered connectivity between the anterior insula and amygdala, the DLPFC and lateral orbitofrontal cortex (OFC), as well as the anterior insula and the dACC when compared to healthy individuals. The latter was negatively associated with aggressive behaviors in participants with schizophrenia (Wald χ 2 = 9.51; p < 0.05, p -FDR corrected). Our results highlight alterations in functional connectivity in brain regions involved in cognitive control and emotion processing which are associated with aggressive behaviors in schizophrenia.